2022
DOI: 10.1111/dth.15624
|View full text |Cite
|
Sign up to set email alerts
|

Personal protective equipment‐related dermatoses in COVID ‐19 frontline health workers. A lesson learned from 1‐year single center in the UAE

Abstract: Since COVID-19 was declared a pandemic in March 2020, frontline health care workers wear personal protective equipment (PPE, surgical masks, N95 or similar respirators, gloves, goggles, face shields, and gowns). Alcohol-based sanitizers and wipes were recommended. Such measures lead to disruption of the natural skin habitat and skin barrier and various cutaneous reactions. The aim was to assess the prevalence and characteristics of PPE-related dermatoses among health care workers in Sheikh Khalifa Medical City… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Table 2 lists the active ingredients, allergenic substances and resulting ASRs of some hand hygiene products. However, frequent hand disinfection with alcohol and hand washing with soap or hand sanitizer during the COVID-19 pandemic can result in the development of ICD and ACD (80)(81)(82). Various chemical additives (including disinfectants and fragrances) present in hand hygiene products may be responsible for the increase of hand ACD.…”
Section: Contact Dermatitis Caused By Hand Hygiene Productsmentioning
confidence: 99%
“…Table 2 lists the active ingredients, allergenic substances and resulting ASRs of some hand hygiene products. However, frequent hand disinfection with alcohol and hand washing with soap or hand sanitizer during the COVID-19 pandemic can result in the development of ICD and ACD (80)(81)(82). Various chemical additives (including disinfectants and fragrances) present in hand hygiene products may be responsible for the increase of hand ACD.…”
Section: Contact Dermatitis Caused By Hand Hygiene Productsmentioning
confidence: 99%
“…Suitable personal protective equipment (PPE) and suitable alternatives are available for selection. Disinfection of lab areas and safe disposal of clinical samples from such patients are also critical (13)(14)(15).…”
Section: Contextmentioning
confidence: 99%
“…This list needs endless revision, updates, and customization to national guidelines. A biosecurity culture is required to successfully implement the policies, a scientific community, and a committed community (15,40).…”
Section: Laboratory Biosafety and Laboratory Biosecuritymentioning
confidence: 99%
See 1 more Smart Citation
“…In UAE the COVID-19 vaccine was available to frontline healthcare providers in September 2020 [4]. Qualitative data from frontline staff in the UAE showed that they were experiencing COVID-19-related stress, as a result of their working in a hazardous environment and due to the trauma of the amount of death seen initially [8][9][10]. A national study has found that levels of anxiety and depression are significantly higher than those reported in previous pre-pandemic studies [11].…”
Section: Introductionmentioning
confidence: 99%